TRANSLATION TECHNIQUES IN MEDAN AND DELI SERDANG TOURISM BOOKLET - Misdahlia Sasmita; Masitowarni Siregar (State University of Medan, 2018)
This study aims to find out the translation techniques, the dominant one used by the translator in translating the booklets and the process of translating the dominant technique. It uses the theory of Molina and Albir, which are adaptation, amplication, borrowing, calque, compensation, description, discursive creation, established equivalent, generalization, linguistic amplication, linguistic compression, literal translation, modulation, particularization, reduction, substitution, transposition, and variation. In analyzing the data, the research was conducting by using mixed method research which involved collecting both quantitative and qualitative data. The data were taken from “Medan and Deli Serdang Tourism Booklet” which consist of Bahasa and translate into English. In Medan Tourism Booklet the result of literal translation 136 sentences (81,43%) belongs to dominant technique that applied in the booklet, followed by transposition 13 sentences (7,78%), adaptation 8 sentences (4,80%), borrowing 3 sentences (1,80%), amplification 2 sentences (1,20%), description 2 sentences (1,20%), reduction 2 sentences (1,20%) and generalization 1 sentence (0,60%). In Deli Serdang Tourism Booklet the result of literal translation 61 sentences (79,22%) belongs to dominant technique that applied in the booklet, followed by transposition 7 sentences (9,09%), reduction 3 sentences (3,89%), discursive creation 2 sentences (2,60%), particularization 2 sentences (2,60%), adaptation 1 sentence (1,30%) and borrowing 1 sentence (1,30%). There are three process in translating the dominant technique 1) analysis, 2) transfer and 3) restructuring.